PHONOLOGICAL AND LEXICAL VARIETIES OF LIO LANGUAGE IN FLORES, EAST NUSA TENGGARA: A STUDY OF GEOGRAPHICAL DIALECT - Suryati, Ni Made; Mbete, Aron Meko; Lauder, Multamia; Dhanawaty, Ni Made (e-Journal of Linguistics; Vol. 6. Januari 2012 No. 1, 2012)
This study aims at describing and analyzing phonological and lexical varieties of Leo language in the regions where it is spoken, classifying its dialects and subdialects, and identifying the identity of its relation to Ende language. The theories used in this study are the theory of traditional dialectology and the theory of generative. The data used were obtained from the primary and secondary sources. The observation method and the participative method were applied to collect the data needed. The data were analyzed using descriptive-comparative method which was continued with dialectometric and mapping method. The segments vowels, consonants and syllables grouped under regular and sporadic varieties. The regular vowel variety and the regular syllable variety were found just one and on the other hand 20 regular consonant varieties.   The vowel sporadic varieties found 37, the consonant sporadic varieties found 176, and the syllable sporadic varieties found 17. Lexically, Lio Language highly varied, indicated by the description of each gloss having more than 10 lexical varieties. Based on the isogloss bundles composed and based on the calculation obtained from both the lexical dialectometry and lexical dialectometry for the TPs which were close to each other, and on the permutation, DBL could be grouped into seven. (1) East Lio Language Dialect; (2) Central Lio Language Dialect; (3) Western Lio Language Dialect; (4) Ende Leo Language Dialect; (5) Welamosa Dialect; (6) Wololele A Dialect; and (7) Konara Dialect. From such groupings of dialects and sub dialects, it could be identified that Lio Language  and Ende Language were different dialects.
Keywords: domains of meanings, dialect, isogloss, and dialectromety